Manners of resistance symbolic defiance of colonial authority in nineteenth century Philippines - Santiago, Fernando A. Jr (Philippine Sociological Review, 2015)
Several accounts of ride and vulgar behavior that annoyed Westerners are mentioned in the nineteenth century documents on the Philippines. Filipino "bad manners" have been cited as proof of the inferiority of the race and used to underrate their intelligence. If Filipinos are to be understood in their own terms, there lies the possibility that the incidents of rudeness mentioned in the historical accounts were actually acts of defiance against colonial authority, the prospect that bad manners were forms of everyday resistance. The study sheds light on acts that made Filipinos rude, deceitful, distrustful, clumsy and insolent; and treat them as symbolic defiance of colonial authority on account of the traditions, ethics, cultural framework and emotionalism of Filipinos.